What is the way out? : innovations of Haier Group in supply chain finance - Song, Hua; Zhao, Xiande; Lu, Qiang (London : Renmin University, 2017)
As Haier Finance Co., Ltd. (Haier Finance) cannot meet the financial demands of many distributors downstream, Haier Group (Haier) seeks to, via its supply-chain finance platform, partner with Ping An Bank and provide supply-chain financial services with collaterals or based on credit. This case studies Haier's supply-chain finance by detailing its background and operational models and analyzing potential risks and challenges, providing reference for traditional manufacturers to transform and upgrade themselves through "Internet Plus" and supply-chain finance.
Originally Published In : Song, H., Zhao, X., & Lu, Q. (2017). What Is The Way Out? Innovations of Haier Group in Supply Chain Finance. Beijing, China: Renmin University Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business logistics -- Case studies; Business enterprises -- Finance -- Case studies